The effect of audit committee members expertise on internal audit budget: evidence from Malaysia - Al-Saih, Tareq Abdulhameed Manea (2018)
Internal auditing is not only an important element of international businesses, but also a crucial component of the company’s internal control and risk management. Audit committee’s main objective is to ensure the trustworthiness and credibility of financial statements by monitoring the process of financial reporting. Internal auditing and audit committees serve each other to generate reliable financial statements. The available resources for internal audit department is monitored by audit committee, whereas internal audit department reports internal control activities to audit committee. The main objective of this study is to examine the impact of audit committee members expertise (accounting experience, auditing experience, BIG Four experience, academic qualification and professional qualification) on internal audit budget in the context of Malaysia. The sample of this study includes the top 100 firms listed in Bursa Malaysia over three-years period – from 2015 to 2017 to examine the proposed relationship. The regression analysis shows that audit committee members accounting experience and professional qualifications have a positive and significant impact on internal audit budget, while audit committee members who worked at BIG Four firms and acquire academic qualification have negative and significant effect on investment in internal audit. The theoretical, academic, regulatory and practical implications were explained in detail showing how policy makers, practitioners and academics can benefit from the current study.